”Ojigi” sebagai Alat Komunikasi - Ilvan Roza (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
Every country in the world has its own culture that characterizes each nation. One of the cultures of every nation is the way to have the social interaction through verbal and non-verbal communication. Verbal communication can be in forms of greetings and so forth, while the non-verbal communication can be signaled by using the scattering; wave of the hand, eye blink, bow weight and so forth. This article discusses the Japanese culture that initiates communications with bowing, known as Ojigi. Keywords: ojigi, means, communications, social, interaction, social interaction